Resolution of Heritage Disputes using Choice of Law in Tanjung Pura Langkat - Nurtaufiq Nurtaufiq; Mhd.Yadi Harahap; Ramadhan Syahmedi Siregar (Budapest International Research and Critics University, 2022)
Inheritance law in Indonesia, at least sociologically, there is still pluralism, in the sense that it is still permissible for interested parties to distribute inheritance/inheritance based on the preferred law (choice of law). Especially in Tanjung Pura Langkat, until now it has been implemented with different systems. there is an inheritance distribution system that is shared equally, some through family agreements, some represent the oldest children to share inheritance, some use Islamic law, if an inheritance dispute occurs, the heirs in resolving disputes through the mediation of the village head, and community leaders, they do not want to settle disputes in court because of the high costs and lengthy process in court. The people of Tanjung Pura are a society whose majority of the population is Muslim and upholds Islamic values, however, many of them share inheritance using customary law.